Diagnosing and treatment of adrenocortical insufficiency in the intensive care unit - Mat Nor, Mohd Basri (Malaysian Society of Anaesthesiologists, 2014)
In critically ill patients, activation of the hypothalamus-pituitary-adrenal (HPA) axis with the production of cortisol is crucial for survival under conditions of physiologic stress. The increase in cortisol production results in several important effects on metabolic, cardiovascular and immune aimed at restoring homeostasis during stress. However, in critical illness, HPA axis undergoes complex changes and the optimum level of plasma cortisol is unclear. In addition to activation of the HPA axis, cortisol metabolism and function may be significantly altered by various aspects of critical illness. There are conditions in which cortisol concentration cannot increase appropriately to meet demand. Assessment of cortisol activity in this group of patients is also difficult because laboratory assays of total plasma cortisol concentration and response to adrenocorticotropic hormone (ACTH) stimulation do not consistently reflect corticosteroid deficient at cellular level. It has been suggested that during critical illness, plasma cortisol concentration poorly reflect the glucocorticoid activity at target tissues. Venkatesh et al. has postulated that the spectrum of adrenocortical dysfunction in sepsis (from plasma to tissue) should be grouped under ‘sick euadrenal syndrome’ rather than an adrenocortical insufficiency.